Crime and criminal justice - Marsh, Ian (Routledge, 2011)
Exploring and explaining crime -- Introduction : crime : the historical context -- Biological explanations for criminal behaviour -- Psychological explanations for criminal behaviour -- Sociological explanations for criminal behaviour -- Explaining the criminal behaviour of women -- Explaining the criminal behaviour of ethnic minorities -- Exploring and explaining criminal justice -- Why punish? : philosophies of punishment -- Theories of punishment -- The history of crime and justice -- Victimology -- Police and policing -- The courts, sentencing, and the judiciary -- Prisons and imprisonment.